Pengaruh Perilaku Konsumen terhadap Keputusan Menginap di Pondok Merapi Homestay - Edelways, Veronica Christian Dinar; Akiriningsih, Titik; Sagala, Afrilia Elizabeth (JURNAL NASIONAL PARIWISATA, 2026)
This study aims to analyze and describe the influence of consumer behavior on guest stay decisions at Pondok Merapi Homestay, located in Samiran Tourism Village, Selo District, Boyolali Regency. The background of the study is the increasing number of homestays in Selo District, from 47 units in 2017 to 84 units in 2024, which has given rise to intense competition. The study used a quantitative method with a sample of 80 respondents taken using a purposive sampling technique. Data were collected using a Likert-scale questionnaire that included four independent variables (psychological, social, economic, and situational factors) and one dependent variable (stay decision). The results showed that simultaneously, all four consumer behavior factors significantly influenced stay decisions with a contribution of 70.08%. Social factors had the highest influence coefficient (0.214) through online recommendations and reviews indicators, while economic factors had the lowest influence (0.119). These findings confirm that social interaction, online reputation, and recommendations are the main determinants in making stay decisions amidst intense competition. Managers are advised to strengthen their homestay's online image as an effective electronic word of mouth (e-WOM).